Incidental finding of bullous concha by cone beamcomputed tomography = Hallazgo incidental de concha bullosa por tomografía computarizada de haz cónico - Távora, Débora M.
This study aimed to describe the imaging aspects of a concha bullosa discovered incidentally by means of cone-beam computed tomography (CBCT) imaging. A female patient underwent a CBCT exam, and a bilateral extensive pneumatization of the middle concha was verified, presenting a larger dimension of the right side and a deviated septum. The patient reported nasal obstruction and loss of smell. The CBCT for covering the maxillofacial region allowed the discovery of this incidental finding, allowing the patient to be referred for appropriate treatment.